TANTANGAN PELAKU PENERBITAN DI ERA INDUSTRI 4.0: SEBUAH TINJAUAN - Suhendra, Muhammad Fadly; Helmiawan, Martinus; Indraswari, Noviastuti Putri (Politeknik Negeri Media Kreatif, 2020)
The era of industry 4.0 is a digital revolution characterized by the fusion or collaboration between cyber and automation technology. Not only in production processes, but also in almost all parts of economic value chains thus new business model based on digital technology to achieve high efficiency and better quality is created. As a part of creative industry, publishing faces the development and demand to change brought by industry 4.0, from business model, product and services innovation, to marketing and target users. This paper explains the development, challenge, opportunity, and effort related profession disruption faced by publishing professionals in industry 4.0 era. The review in this paper was done by conducting literature and empirical studies. The result shows that publishing professionals must strive to transform mindset and work process in publishing world. Those transformation can be achieved by competency improvement through increasing knowledge in publishing management, building coopetition between fellow publishing professionals, and consistent orientation for usersâ€™ needs. It is important for publishing professionals to view this phenomenon as a challenge that brings many possibilities for the development towards publishing 4.0Â Â Keywords: Publishing professionals, Disruption, Publishing 4.0, Transformation